clarifying the receipt in mortgage of debt: Comparative study between Islamic jurisprudence and the Algerian civil law - boudaoui, karim; tahri, belkhir (Journal of Social Sciences and Humanities, 2020)
The receipt in the mortgage of debt is considered to be one of the most complex and thorny juristic issues; and this is mainly due to the fact that it is constituted of three different terms: the receipt, the mortgage, and the debt. Each of which represents an independent subject in law, as well as in jurisprudence. As a consequence, both of Islamic jurisprudence and civil law have regulated this type of transactions and made it subject to a certain amount of rules and conditions that show its provisions, through the induction and affiliation of scholars' (jurists and lawmen) points of view and sayings historically--taking into consideration the environment surrounding each jurist/lawman, i.e. the conditions in which, and the proofs upon which they depended to build their provisions. So far, this was for the purpose to guarantee the rights of the contractors from one hand, and to settle the disputes that may arise and occur among them. And as it only occurs upon the movables and moral; what multiplies its issues and jurisprudential differences. And for the sake of its importance in the people's lives and their need for it, we will clarify the reality of this pledge by showing its concept and nature in both Islamic jurisprudence and the Algerian civil law.